Development of linear cavity fiber lasers for ultrashort pulse generation with high repetition rate - Li, Nong. (2013)
Mode-locked fiber lasers are able to generate transform-limited optical pulses in picosecond and sub-picosecond regimes. The fiber lasers are usually passively mode-locked using a saturable absorber such as saturable Bragg reflectors (SBRs), SESAM (semiconductor saturable absorber mirror), and nonlinear optical loop mirrors. There is a number of qualities that make the passive mode-locked fiber lasers attractive for ultrashort pulse generation, such as the generation of ultra short optic pulses in picosecond or sub-picosecond, their compact and rugged fabrications, and no requirement of active modulators. Moreover, they can also be worked with tele-communication components, and their output is compatible with telecom systems. Passively mode-locked fiber lasers are treated as one of the best optical sources in the contemporary society.